Conceptualizing ethnicity in alcohol and drug research: Epidemiology meets social theory. Issue 2 (3rd April 2018) - Hunt, Geoffrey; Kolind, Torsten; Antin, Tamar
ABSTRACT: Since the 1990s, social scientists have rejected notions of ethnicity as something static and discrete, instead highlighting the context-dependent and fluid nature of multiple identities. In spite of these developments, researchers within the substance use fields continue to assess ethnic group categories in ways that suggest little critical reflection in terms of the validity of the measurements themselves, nor the social, bureaucratic, and political decisions shaping standard measures of ethnicity. This paper highlights these considerations, while also acknowledging the role of socially-delineated ethnic categorizations in documenting health inequities and social injustices. We call on researchers in alcohol and drugs research to critically appraise their use of ethnic categorizations, querying how to best measure ethnicity within their own studies in ways that are justified beyond simplified explanations of social convention and that "do no harm" in terms of perpetuating racism and obscuring the roots causes of social and health problems related to alcohol and drugs.